Karṇāṭaka śabdānuśāsana prakāśike : Bhaṭṭākaḷaṅkadēva viracita Saṃskr̥ta Karṇāṭaka śabdānuśāsanada vistāravāda Kannaḍa ṭīke - Kuṇḍalagiryācārya (SAMP early 20th-century Indian books project ;, 1941)
Commentary on Karṇāṭaka śabdānuśāsanaṃ, work on Kannada grammar by Bhaṭṭākalaṅkadēva, fl. 1592-1604.